Effect of Tillage practices and Foliar Spray of Micronutrients on Growth, Yield Components and Yield of Grasspea (Lathyrus sativus L.) in Rice-Fallow System - Das, Tathagata; Barik, Arun Kumar; De, Prasenjit (International Journal of Bio-resource and Stress Management, 2022)
A field experiment was conducted at farmers’ field of Rampurhat-II block, Birbhum, West Bengal, India for two consecutive rabi seasons (October– March) of 2018–19 and 2019–20 to find out the effect of tillage practices and foliar spray of micronutrients on growth, yield components and yield of grasspea variety Ratan (BioL 212). The experiment was laid out in split plot design replicated thrice having three tillage practices (no tillage utera, zero tillage and conventional tillage) in main plots and four levels of foliar spray of micronutrients (no micronutrient spray, foliar spray of Zn @ 0.05% twice at 30 and 45 DAS, foliar spray of B @ 0.1% twice at 30 and 45 DAS and foliar spray of Zn @ 0.05%+foliar spray of B @ 0.1% twice at 30 and 45 DAS) in sub-plots with twelve treatment combinations. Different tillage practices and foliar spray of micronutrients had significant response on various growth parameters, yield attributing characters (no. of pods plant-1, no. of seeds pod-1, 1000 seed weight) and yield (seed and stover) of grasspea. Among tillage practices, highest seed yield and stover yield was recorded under zero tillage (1.03 t ha-1 and 1.51 t ha-1 respectively whereas foliar spray of Zn @ 0.05% and B @ 0.1% twice at 30 and 45 DAS combinedly registered significantly highest seed yield and stover yield (0.99 t ha-1 and 1.69 t ha-1, respectively) among foliar spray of micronutrients.